TIKTOK MEDIA PARTISIPASI BAGI GEN Z DALAM PERCEPATAN PEMBANGUNAN JALAN DI DAERAH KABUPATEN KUNINGAN - Putri Ayu Anggraeni; Sarip Sarip; Nur Rahman (Hukum, 2026)
The development of TikTok has expanded opportunities for public participation, particularly for Generation Z in expressing concerns about infrastructure services. This study examines the use of TikTok as a medium for Generation Z participation in advocating road improvements in Kuningan Regency and evaluates government responses from the perspective of responsive law. The study employed an empirical legal method using a socio-legal approach and qualitative design. Data were collected through content analysis of TikTok videos concerning damaged roads, semi-structured interviews with a representative of the Kuningan Regency Public Works and Spatial Planning Office, and a review of legislation, government documents, and relevant literature. The data were analyzed thematically and chronologically by distinguishing digital visibility, communicative responses, administrative follow-up, policy commitments, and physical road improvements. The findings indicate that TikTok functions as an advocacy and amplification channel that can increase public attention and encourage an initial government response. However, virality cannot be directly regarded as the cause of accelerated road improvements because road handling remains influenced by road status, jurisdictional authority, technical verification, planning, and budget availability. From the perspective of responsive law, the government should integrate digital aspirations into formal complaint mechanisms so that every report is addressed transparently, fairly, and traceably rather than according to the popularity of online content.